The effect of Lorentz symmetry violation on the hadron fragmentation function - S. Mohammad Moosavi Nejad; A. Yeganeh (European Physical Journal C: Particles and Fields)
Abstract Different processes have been yet considered to investigate the effects of Lorentz symmetry violation and various bounds have been determined for the magnitude of Lorentz violation (LV) coefficients. In the present work we study, for the first time, the effect of Lorentz-violating terms on the fragmentation functions (FFs) of heavy mesons in two distinct cases correspondent to axial and vectorial nonminimal couplings in the theory of quantum chromodynamics (QCD). Our analytical results for heavy meson FFs in the framework of LV can be used to study the effect of Lorentz symmetry violation on hadron production processes in high energy colliders.